2010
DOI: 10.1007/s11249-010-9694-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasma Treatment on Carbon Fabric for Enhancing Abrasive Wear Properties of Polyetherimide Composites

Abstract: Interfacial adhesion between matrix and fiber plays a crucial role in controlling performance properties of composites. Carbon fibers have major constraint of chemical inertness and hence limited adhesion with the matrix. Surface treatment of fibers is the best solution of the problem. In this work, cold remote nitrogen oxygen plasma (CRNOP) was used for surface treatment. Twill weave carbon fabric (CF) (55-58 vol%) was used with and without plasma treatment with varying content of oxygen (0-1%) in nitrogen pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The treatment introduces some functional groups, perforation and deep ridges on the fiber surface, which changes their roughness and promotes adhesion toward polymers. In our earlier study, we have reported on the beneficial effects of cold remote nitrogen oxygen plasma (CRNOP) treatment to CFs on their performance properties including tribological in adhesive and abrasive wears [10][11][12][13]. In this article, LAO wear performance of treated fabric composites is discussed in detail.…”
mentioning
confidence: 95%
“…The treatment introduces some functional groups, perforation and deep ridges on the fiber surface, which changes their roughness and promotes adhesion toward polymers. In our earlier study, we have reported on the beneficial effects of cold remote nitrogen oxygen plasma (CRNOP) treatment to CFs on their performance properties including tribological in adhesive and abrasive wears [10][11][12][13]. In this article, LAO wear performance of treated fabric composites is discussed in detail.…”
mentioning
confidence: 95%
“…Because, the room temperature is higher than the T g of the polypropylene (around 0°C). Moreover, aromatic thermoplastic polymers, such as polycarbonate [16,17], polybutylene terephthalate [18], polyethersulfone [19][20][21], polyetherimide [19,22,23], polyimide [24,25], polyetheretherketone [19,[26][27][28][29] and polyphenylenesulfide [30][31][32] have also been studied for high performance carbon fibers (CFs)/polymer matrix composites. In general, the aromatic polymers have high temperature resistance, high modulus of elasticity, and water resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it should be necessary to have good interfacial adhesion between CFs and matrix polymers for produce the high performance CFRTPs. Numerous methods for surface treatment of CFs, such as chemical modification [24,34], electrochemical oxidation [35][36][37][38][39][40][41], and plasma treatment [16,17,19,[21][22][23]29] have been studied to assure good interfacial adhesion. The basic idea of the CF surface modification is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Several articles are available on studies on tribological properties in adhesive [1][2][3] or reciprocating wear modes [4][5][6]. Though abrasive wear is the most severe kind of wear, it has not been exploited for performance evaluation of such composites in the literature except the authors' own work on plasma treatment [7], Nitric acid oxidation treatment, or gamma irradiation treatment method [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Physical and mechanical properties of untreated, YbF 3 -treated, and 1% O 2 plasma-treated CF-reinforced composites[7] …”
mentioning
confidence: 99%